Investigating the Penetration Rate of Electric Vehicle in Developing Countries: Nigeria as A Case Study - Bawa, Abubakar; Nwohu, Mark Ndubuka (Lecture notes in engineering and computer science, 2023)
The concept of electric vehicles has been widely accepted by people all over the world, and sales are expected to continue to rise. Electric vehicles (EVs) are gaining traction in Nigeria as well. Furthermore, through a bidirectional charging system, the deployment of electric vehicles in Nigeria can support environmentally friendly renewable energy development. Electric vehicle development could also lower emissions, reduce energy sector investment, and potentially eliminate the need for costly petroleum subsidies. The benefits are obvious, however, Nigeria's challenges that will impede high rate of penetration hinge on the epileptic electricity supply. This investigational assessment has recognized the enormous potential of electric vehicles in Nigeria as an improvement and advancement agent. With the entire vehicle industry looking for new learning and development opportunities, it is reasonable to anticipate that those open opportunities will significantly increase in Nigeria, the continent's largest economy. Ideally, with the right methodologies, strategies, perspectives, policies, and commitment, the future of electric vehicles in Nigeria appears to be clear. To that end, this paper assessed the penetration rate of electric vehicles in Nigeria, considering the potential impact of EVs on the country's auto industry.